2008
DOI: 10.1094/phyto-98-3-0330
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Fresh and Ensiled Maize by Multiple Penicillium Mycotoxins

Abstract: Toxins produced by Penicillium species are reported in maize silage and have been associated with health problems in cattle. Our objectives were to evaluate the prevalence and dynamics of patulin (PAT), mycophenolic acid (MPA), cyclopiazonic acid (CPA), and roquefortine C (ROC) in fresh and ensiled maize. To achieve these objectives we developed a high-performance liquid chromatography method coupled with mass spectrometry to detect all four toxins simultaneously in silage. In addition we collected weather dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…In comparison to these Fusarium or Aspergillus mycotoxins, there are considerably fewer studies available related to mycotoxins produced from Penicillium spp., even though they are regarded as the most common mycotoxins found in silage for animal feed (Mansfield et al 2008). Therefore, there is a need for more studies to examine their potential toxicity, as well as effective preventive methods to deal with Penicillium mycotoxins (PMs).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to these Fusarium or Aspergillus mycotoxins, there are considerably fewer studies available related to mycotoxins produced from Penicillium spp., even though they are regarded as the most common mycotoxins found in silage for animal feed (Mansfield et al 2008). Therefore, there is a need for more studies to examine their potential toxicity, as well as effective preventive methods to deal with Penicillium mycotoxins (PMs).…”
Section: Introductionmentioning
confidence: 99%
“…Feeds multicontaminated by mycotoxins are frequent in the field (Scudamore et al 1998;Mansfield et al 2008) and the ability of YCW to bind several mycotoxins makes them 24 suitable for use under practical feeding conditions. In vivo studies have shown that YCW can reduce the adverse effects of mycotoxins in different animal species; swine (Swamy et al 26 2002), horse (Raymond et al 2003), laying hens (Chowdhury et al 2005), and dairy cows (Korosteleva et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium spp. has been considered as storage fungi; however, in many cases it is present on maize before harvest (Mansfield, Jones & Kuldau, 2008). In the study carried out in Italy, the RD for Penicillium in organic maize was lower than 2%.…”
Section: Discussionmentioning
confidence: 96%